Manajemen Program PAUD bagi Suku Anak Dalam dan Pemenuhan Hak Pendidikan Anak - Prianka, Marselia Febi; Putera, Roni Ekha; Yoserizal, Yoserizal (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The implementation of the Early Childhood Education (PAUD) program for the Suku Anak Dalam (SAD) aims to provide good and systematic learning. However, in its implementation there are many challenges, ranging from the difficulty of introducing education to SAD to the emergence of problems from the Education and Culture Office of Sarolangun Regency in meeting resources. This difficulty was also inseparable from the context of the Covid-19 pandemic which affected the implementation of education in Indonesia at that time. This study uses a qualitative approach with descriptive research methods. Sources of data in this study obtained directly, through observation and interviews as primary data. Secondary data sources are obtained from documentation. The analysis technique is carried out by reducing data, presenting data and drawing conclusions. The purpose of this study was to analyze the management of the PAUD SAD program and its relationship to the fulfillment of the right to education for children. Management process analysis is carried out by describing the phenomena that found in the field starting from the planning, organizing, resource gathering, work control, and supervision processes. The results of this study indicate that the management of the PAUD SAD program has not been implemented optimally due to the Covid-19 pandemic that occurred in that year.